A Short Synthesis of (2S,3S,4R)-Dihydroxyhomoprolines from d-Erythrose-Derived 5,6-Dihydro-2H-pyran-2-one - Freitas, David S.; Noro, Jennifer; Drogalin, Artem; Fernandes, Mónica C. S.; Baptista, António V. M.; Parente, Joana F. C.; Rodríguez-Borges, José E.; Gil Fortes, António; Alves, Maria J. (Synthesis, 2019)
(2S,3S,4R)-Dihydroxyhomoprolines were obtained from a six-carbon-atom lactone intermediate obtained from d-erythrose in a short synthesis, by facile operational methodology, in very good overall yields.
Keywords: lactones; dihydroxyproline; diastereoselectivity